Bleeding during percutaneous intervention: tailoring the approach to minimise risk. Issue 1 (20th January 2008) - Kinnaird, T; Anderson, R; Hill, J; Thomas, M
Abstract : The incidence of ischaemic complications during percutaneous intervention (PCI) has reduced over recent years. As a result, bleeding has now emerged as one of the most common complications of PCI in contemporary practice. In addition, measures intended to minimise ischaemic complications—such as balloon pumps or glycoprotein inhibitors—may actually increase bleeding frequency. Recent studies have not only highlighted the incidence with which major bleeding occurs but also demonstrated the profound effect of bleeding on mortality. Thus bleeding can no longer be considered an irritation that can simply be ignored or transfused. This review summarises the major trial and registry data obtained in a PubMed search combining the terms "bleeding" and "percutaneous coronary intervention" and then proposes strategies to minimise bleeding occurrence.